Cardiorespiratory fitness, sociodemographic indicators and nutritional status in adolescents Aptidão cardiorrespiratória, indicadores sociodemográficos e estado nutricional em adolescentes Aptitud cardiorrespiratoria, indicadores sociodemográficos y estado nutricional en adolescentes - Minatto G. (2015)
© 2014, Redprint Editora Ltda. All rights reserved.Introduction: inadequate levels of cardiorespiratory fitness in adolescence are inversely associated with cardiovascular risk factors and metabolic disorders. Objective: to assess the association among cardiorespiratory fitness and sociodemographic indicators and nutritional status in adolescents. Methods: cross-sectional study carried out with 627 adolescents (361 girls), aged 14-17 years, of both sexes, living in a city of intermediate/low Human Development Index (HDI). Anthropometric variables (body mass - BM and height - HEI) were collected to obtain body mass index (BMI = BMkg/HEIm2), as well as demographic data (age, socioeconomic status and area of residence). The analysis of low cardiorespiratory fitness (1600-meter run/walk test) considered the time for the completion of the test equal to or longer than 7:45 min and 7:30 min for boys aged 14 and 15 -17 years, respectively, and 10:30 min for girls. Results: low cardiorespiratory fitness was observed in 35.3% of boys and 35.5% of girls. Boys belonging to lower economic levels (Class C: RP=0.54, CI95%=0.31-0.93; Class D + E: RP=0.46, CI95%=0.22-0.98) were less exposed to low levels of cardiorespiratory fitness. On the other hand, boys with low birth weight (RP=1.49, CI95%=1.04-2.13) and boys and girls living in the urban area (boys: RP=1.79, CI95%=1.28- 2.50; girls: RP=1.32, CI95%=0.99-1.75) were more likely to have low cardiorespiratory fitness. Conclusion: the indicators that were associated with low cardiorespiratory fitness for boys were living in the urban area and intermediate and low economic levels. For girls, the outcome was associated only with the area of residence. Interventions for health promotion primarily aimed at adolescents living in urban areas and belonging to higher economic levels should be implemented.